The Association between Diabetes Mellitus and Serum Prostate-Specific Antigen Levels (Medico Legal Update, 2020)
Background: Diabetic patients were indicated to have an improved risk for cancers of the liver, pancreas,and colon; nevertheless, recently many studies have suggested that diabetes mellitus (DM) decreasedpossibility for developing the cancer of prostate in men.Objective: To analyze if the levels of prostate-specific antigen (PSA) in serum of men with type two DMwere low in comparison with healthy group, and to investigate the factors that could influence the PSA levelin diabetic patients.Method: 120 diabetic men patients were analyzed for PSA levels in the serum compared with equal numberage-matched control group. The relationships between the serum PSA levels and body mass index (BMI),age, hypertension, smoking and glycosylated hemoglobin (HbA1c) were considered.Results: Serum PSA levels were statistically significantly (p